A is for arsenic : the poisons of Agatha Christie - Harkup, Kathryn (Bloomsbury Sigma, 2015)
Investigates the poisons Christie employs in fourteen of her mysteries, discussing why the poisons kill, how they interact, obtainability of such poisons, and which cases may have inspired Christie's stories.